ON THE SPAWNING ACTIVITIES OF KINGFISH, SCOMBEROMOROUS COMMERSON, IN OMAN WATERS - THANGARAJA, M.; AL AISRY, AHMED (Journal of Indian Fisheries Association, 2016)
The spawning activities of kingfish, Scomberomorus commerson, in Oman waters are traced out for the first time. The possible spawning period and spawning ground are identified on the basis of collection of its eggs and larvae from Oman waters. The eggs and early larval characteristics are described suitably with photographic illustration of 4.9 - mm larva. The optimum surface water temperature and salinity recorded for the occurrence of kingfish eggs and larvae are 23.57 - 26.05 oC and 36.0 - 36.1 %o, respectively. Keywords.: King fish, spawning grounds, Development.